C1-Symmetric Si-bridged (2-indenyl)(1-indenyl) ansa-metallocenes as efficient ethene/1-hexene copolymerization catalysts. Issue 9 (24th February 2020) - Uborsky, Dmitry V.; Mladentsev, Dmitry Y.; Guzeev, Bogdan A.; Borisov, Ilya S.; Vittoria, Antonio; Ehm, Christian; Cipullo, Roberta; Hendriksen, Coen; Friederichs, Nic; Busico, Vincenzo; Voskoboynikov, Alexander Z.
Abstract : Synthesis, ethene/1-hexene copolymerization screening, and QSAR study of 28 silicon bridged (2-indenyl)(1-indenyl) zirconocenes: new promising catalysts for LLDPE were identified. Abstract : In the search for more efficient single-center ethene/α-olefin copolymerization catalysts, metallocenes bearing a 2-indenyl substituent pattern have largely been ignored in the past. Here, we show that such a structural motif yields competent linear low-density polyethylene (LLDPE) catalysts. They are also relatively easy to synthesize, allowing for a wide structural amplification. A screening of 28 catalysts reveals that the lead catalyst in this study displays high comonomer affinity and molecular weight capability at industrially relevant temperatures. QSAR models show that steric factors likely contribute stronger than electronic factors to the observed substituent trends, both for comonomer affinity and MW capability.